2011
DOI: 10.2478/s11536-011-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel as an anticancer agent: isolation, activity, synthesis and stability

Abstract: AbstractPaclitaxel is isolated from the Pacific yew. It can be obtained from the European yew, but only after chemical modification of the isolated compound by a semi-synthesis procedure. The procedure for total synthesis of paclitaxel is very complicated, involving multiple steps, and the yields of paclitaxel are meagre. This substance is also a metabolite of certain kinds of fungus. The microbiological pathway for producing paclitaxel compared with isolation from plant materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Even slow degradation of the free end of the CL block also converts a cylinder-forming amphiphile to a higher curvature sphere-former that will be more disruptive to membranes [10]. With free drug, cell viability decreased from day 1 to day 2, but then increased from day 2 to day 3 ( Figure 3C), which is perhaps due to degradation of TAX by hydrolysis [36,37] that occurs over days [38,39]. Nanocarrier cores can protect against such hydrolysis, with PCL cores protecting cisplatin from degradation [40] and a protective effect might explain the decrease in cell viability with TAX filomicelles from day 1 to 2 and day 2 to 3 ( Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…Even slow degradation of the free end of the CL block also converts a cylinder-forming amphiphile to a higher curvature sphere-former that will be more disruptive to membranes [10]. With free drug, cell viability decreased from day 1 to day 2, but then increased from day 2 to day 3 ( Figure 3C), which is perhaps due to degradation of TAX by hydrolysis [36,37] that occurs over days [38,39]. Nanocarrier cores can protect against such hydrolysis, with PCL cores protecting cisplatin from degradation [40] and a protective effect might explain the decrease in cell viability with TAX filomicelles from day 1 to 2 and day 2 to 3 ( Figure 3D).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that active compounds isolated from medicinal plants are used in TM (Orrego-Escobar, 2015). One of the significant milestones in the research field of antineoplastic properties is paclitaxel (Nikolic et al, 2011).…”
Section: Major Category: Opportunities In the Practice Of Atmmentioning
confidence: 99%
“…Different procedures have been developed to isolate paclitaxel from natural sources. The majority of ordinary solvent extraction processes reported in the literature have made use of methanol as the extraction solvent, where the accelerated solvent extraction method enhances the conventional extraction process using solvent at elevated temperatures [300,301]. On other hand, HPLC and mass spectroscopy analysis showed that acetone is the best solvent for the extraction of paclitaxel from Taxus baccata needles [298].…”
Section: Paclitaxelmentioning
confidence: 99%
“…On other hand, HPLC and mass spectroscopy analysis showed that acetone is the best solvent for the extraction of paclitaxel from Taxus baccata needles [298]. Pure paclitaxel from plant material was obtained using Acetone/water precipitation procedure [301]. The extraction of paclitaxel from the ground bark of Taxus brevifolia using supercritical carbon dioxide was also reported [302].…”
Section: Paclitaxelmentioning
confidence: 99%